Association of Adverse Childhood Experiences Including Low Household Income and Peer Isolation With Obesity Among Japanese Adolescents: Results From A-CHILD Study - Doi, Satomi; Isumi, Aya; Fujiwara, Takeo (Frontiers in Public Health, 2022)
Background Adverse childhood experience (ACE) is a major risk factor for obesity in both adults and adolescents. Although, arguably, peer isolation and low household income could be conceived as of ACEs, few studies have included these experiences as ACEs. Objectives This study aims to examine whether ACEs, including peer isolation and low household income, are associated with obesity in adolescents. Methods We used pooled data from the Adachi Child Health Impact of Living Difficulty (A-CHILD) study in 2016 and 2018, which is a school-based cross-sectional study in Adachi City, Tokyo, Japan, N = 6,946, 4th (9–10 years old), 6th (11–12 years old), and 8th (13–14 years old) grades. Among the eight items of ACEs, adolescents assessed one item, including peer isolation, and their caregivers assessed seven other items using questionnaires. The adolescents' body mass index (BMI) was measured in school health checkups and calculated to fit the World Health Organization (WHO) standards. Multinomial logistic regression was applied to investigate the association of the cumulative ACEs and each type of ACE with BMI, in which the study was conducted in 2020. Results The number of ACEs was not associated with overweight or obesity among adolescents after adjusting for covariates. As for each type of ACE, single parenthood and low household income showed a significant independent association with obesity. Conclusions The number of ACEs was not associated with overweight or obesity in Japanese adolescents, while single parenthood and low household income showed a significant positive association with obesity. Further longitudinal studies are needed to replicate this association among adolescents.